Influences of Water Vapor on Roof Fall Accidents in Selected Underground Coal Mines in Malawi - Umali M. Yasidu; Yoshiaki Fujii; Jun-ichi Kodama; Daisuke Fukuda; George J. Maneya; Johnson Dandadzi; Anjula B. N. Dassanayake (Advances in Civil Engineering)
To develop affordable countermeasures against the roof falls, the accident records of Mchenga Mine were investigated as the first step. Based on the accident records, it was found that roof falls occurred most in April and May. Humidity measurements were taken both in the underground mine and at surface, and humidity peak appeared in April. The accident occurrence and the underground humidity had a positive correlation in which no roof falls could be expected under a humidity of less than a certain value. Effect of humidity on the indirect tensile strength of the rock samples collected from the mine was investigated, and it showed that the indirect tensile strength decreased with humidity. The diffusion coefficient was measured for the rock samples collected from Mchenga Mine as well as from Kaziwiziwi Mine, and the migration of water vapor into rock mass in the roof was calculated for Mchenga case. It was clarified that the weakening of tensile strength was transmitted upward at several centimeters per day from the immediate roof. This could explain the slight difference of the accident peak in April and May from the humidity peak in April. Introducing fresh and dry outside air, if possible, will not only improve the working environment but also contribute to a decrease in roof falls.